2019
DOI: 10.1017/s0007114519003064
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein insufficiency: an important consideration in fatty liver disease?

Abstract: Dietary protein insufficiency has been linked to excessive TAG storage and non-alcoholic fatty liver disease (NAFLD) in developing countries. Hepatic TAG accumulation following a low-protein diet may be due to altered peroxisomal, mitochondrial and gut microbiota function. Hepatic peroxisomes and mitochondria normally mediate metabolism of nutrients to provide energy and substrates for lipogenesis. Peroxisome biogenesis and activities can be modulated by odd-chain fatty acids (OCFA) and SCFA that are derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 82 publications
1
25
0
2
Order By: Relevance
“…We established a model for RAS immunization under a low protein diet and a subsequent challenge under protein-sufficient conditions that alters the nutritional status of the host, without affecting parasite development. We showed that our newly-established protocol successfully accomplished the proposed objectives, since: i) mice under LP diet gained less weight and consumed more water than their counterparts receiving AP diet, in line with previous reports involving reduced dietary protein ( 22 , 23 , 42 ); ii) the livers of mice under LP diet showed increased expression of lipogenesis-related genes, in agreement with the association of low dietary protein with hepatic lipid accumulation and increased risk of fatty liver disease ( 43 , 44 ); iii) following challenge, Pb liver load and blood parasitemia were equivalent in non-immunized mice maintained under LP or AP diet.…”
Section: Discussionsupporting
confidence: 80%
“…We established a model for RAS immunization under a low protein diet and a subsequent challenge under protein-sufficient conditions that alters the nutritional status of the host, without affecting parasite development. We showed that our newly-established protocol successfully accomplished the proposed objectives, since: i) mice under LP diet gained less weight and consumed more water than their counterparts receiving AP diet, in line with previous reports involving reduced dietary protein ( 22 , 23 , 42 ); ii) the livers of mice under LP diet showed increased expression of lipogenesis-related genes, in agreement with the association of low dietary protein with hepatic lipid accumulation and increased risk of fatty liver disease ( 43 , 44 ); iii) following challenge, Pb liver load and blood parasitemia were equivalent in non-immunized mice maintained under LP or AP diet.…”
Section: Discussionsupporting
confidence: 80%
“…Another potential source of OCSFA is from the action of peroxisomal 2-OH acyl CoA lyase that cleaves and removes one carbon during fatty acid α-oxidation ( Ampong et al, 2020 ). Liver expression of this gene was lower in HFD compared to CD-fed animals and may contribute to lower C17:0 and other have shown that 2-OH acyl CoA lyase is a major contributor to determining C17:0 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary protein deficiency has been associated with excessive TG storage and NAFLD in population studies, and older adults are at risk for protein malnutrition [ 32 ]. Therefore, in addition to common pathogenic risks of NAFLD, we also included nutritional risk as a variable in our analysis of the association between FSH and NAFLD.…”
Section: Discussionmentioning
confidence: 99%